OBSCN undergoes extensive alternative splicing during human cardiac and skeletal muscle development - Ali Oghabian; Per Harald Jonson; Swethaa Natraj Gayathri; Mridul Johari; Ella Nippala; David Gomez Andres; Francina Munell; Jessica Camacho Soriano; Maria Angeles Sanchez Duran; Juha Sinisalo; Heli Tolppanen; Johanna Tolva; et al. (Skeletal Muscle, 2025)
Abstract Background Highly expressed in skeletal muscles, the gene Obscurin (i.e. OBSCN) has 121 non-overlapping exons and codes for some of the largest known mRNAs in the human genome. Furthermore, it plays an essential role in muscle development and function. Mutations in OBSCN are associated with several hypertrophic cardiomyopathies and muscular disorders. OBSCN undergoes extensive and complex alternative splicing, which is the main reason that its splicing regulation associated with skeletal and cardiac muscle development has not previously been thoroughly studied. Methods We analyzed RNA-Seq data from skeletal and cardiac muscles extracted from 44 postnatal individuals and six fetuses. We applied the intron/exon level splicing analysis software IntEREst to study the splicing of OBSCN in the studied samples. The differential splicing analysis was adjusted for batch effects. Our comparisons revealed the splicing variations in OBSCN between the human skeletal and cardiac muscle, as well as between post-natal muscle (skeletal and cardiac) and the pre-natal equivalent muscle. Results We detected several splicing regulations located in the 5’end, 3’ end, and the middle of OBSCN that are associated with human cardiac or skeletal muscle development. Many of these alternative splicing events have not previously been reported. Our results also suggest that many of these muscle-development associated splicing events may be regulated by BUB3. Conclusions We conclude that the splicing of OBSCN is extensively regulated during the human skeletal/cardiac muscle development. We developed an interactive visualization tool that can be used by clinicians and researchers to study the inclusion of specific OBSCN exons in pre- and postnatal cardiac and skeletal muscles and access the statistics for the differential inclusion of the exons across the studied sample groups. The OBSCN exon inclusion map related to the human cardiac and skeletal muscle development is available at http://psivis.it.helsinki.fi:3838/OBSCN_PSIVIS/ . These findings are essential for an accurate pre- and postnatal clinical interpretation of the OBSCN exonic variants.